Analisis Sifat Fisiologi Dalam Daun Sebagai Bahan Seleksi pada Beberapa Klon Kopi Arabika (Coffea Arabica L.) - Eko Bagus Setyawan; Gatot Subroto (Jember University Press, 2023)
The coffee plant (Coffea) is one of the main types of plants in Indonesian society. Coffee plantations in Indonesia are very influential on the national economy. Several types of Arabica coffee clones began to be developed in order to have certain resistance to overcome attacks by various OPT which had a considerable impact on harvest success. The existence of resistance genes in plants, suitability with virulent genes and environmental influences become obstacles in making coffee clones that are resistant to certain pests. The physiological properties of coffee plants will affect the rate of growth and development of plants so that it will have an impact on their production. Selection of plant varieties is carried out to obtain certain superior characters with high yield potential. An analysis of the physiological properties must be carried out to identify and determine the desired selection criteria. This research was conducted at the Laboratory of the Faculty of Agriculture, University of Jember in June – end, using a single factor Completely Randomized Design (CRD), namely several Arabica coffee clones. Arabica coffee clone consists of 15 clones. Each clone was repeated three times, so that in this experiment there were 45 experimental units. Observational data obtained were analyzed using variance. If there is a significant difference between the treatments then proceed with Duncan's multiple range test at the 5% level. Based on the data and discussion of the research that has been done, it can be concluded that the fifteen arabica clones have different characteristics. The best Arabica coffee clone is the Sigararutang coffee clone which has a high value with (76.76 mg/g) chlorophyll content, (4.15 mg/g) flavonoid content, (7.07 mg/g) phenol content, ( 0.89 mg/g) dissolved protein content and (86.94 mg/g) antioxidant content. Keywords: Coffee clones, chlorophyll, flavonoids, phenols, soluble proteins, antioxidants